The control of hypertension Among patients attending Hospital universiti sains malaysia's Hypertension clinic - Kadir, Shaharuddin Che (2007)
This study was conducted with the primary objective of assessing the proportion of patients who achieved their blood pressure targets. The secondary objectives were to evaluate the factors associated with uncontrolled blood pressure and to determine the number of antihypertensive agents required to achieve controlled blood pressure. Methods A cross-sectional study of hypertens ive patients attending Hospital USM hypertension clinic was conducted from April until September 2006. Patients' blood pressure, smoking history, BMI, urinalysis for protein, fasting lipid profile, renal function test and fasting blood sugar were obtained. The blood pressure was defined as controlled if < 140/90 mmHg or < 130/80 mmHg in patients with diabetes or chronic kidney disease, or < 125/75 mmHg in patients with proteinuria > 1g/day. Results A total of 245 patients compliant to medications were recruited. Thirty four percent of them achieved controlled blood pressure (n = 83). Patients with chronic kidney disease were the majority (69.14%) among patients with uncontrolled blood pressure. Univariate analysis showed several factors were associated with uncontrolled blood pressure: older age, malay race, history of smoking; higher creatinine, uric acid,total cholesterol, triglyceride and fasting blood sugar; lower eGFR; the use of more than 2 antihypertensive agents and the use of diuretics; and the presence of diabetes mellitus, chronic kidney disease and proteinuria. However the results of multiple logistic regression analysis indicated that female gender (p = 0.00 I), malay race (p = 0.031), smoking (p < 0.001), eGFR (p < 0.001) and diabetes mellitus (p = 0.001) were the independent factors associated with uncontrolled blood pressure. Univariate analysis showed that patients who were on treatment with 1 or 2 antihypertensive agents were more likely to have controlled blood pressure than those on more than 2 drugs (p = 0.001 ), however, this was not statistically significant in multivariate analysis.